2020
DOI: 10.3389/fendo.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Short-Chain Fatty Acids From Gut Microbiota in Gut-Brain Communication

Abstract: A substantial body of evidence supports that the gut microbiota plays a pivotal role in the regulation of metabolic, endocrine and immune functions. In recent years, there has been growing recognition of the involvement of the gut microbiota in the modulation of multiple neurochemical pathways through the highly interconnected gut-brain axis. Although amazing scientific breakthroughs over the last few years have expanded our knowledge on the communication between microbes and their hosts, the underpinnings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
1,075
1
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,568 publications
(1,288 citation statements)
references
References 194 publications
17
1,075
1
17
Order By: Relevance
“…Lim et al, 2016, also revealed that gut tight junction, endotoxemia and inflammation were ameliorated after Lactobacillus sakei OK67 treatment in type 2 diabetic rat model [ 15 ]. Furthermore, a previous study demonstrated that the production of short-chain fatty acids (SCFAs) and gut microbial metabolites, including acetate, propionate and butyrate, seems to play an important role in the attenuation of T2DM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al, 2016, also revealed that gut tight junction, endotoxemia and inflammation were ameliorated after Lactobacillus sakei OK67 treatment in type 2 diabetic rat model [ 15 ]. Furthermore, a previous study demonstrated that the production of short-chain fatty acids (SCFAs) and gut microbial metabolites, including acetate, propionate and butyrate, seems to play an important role in the attenuation of T2DM [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of gut microbiota have developed extremely fast and their composition and products have been associated with human physical and mental health [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Several sophistic approaches have been established to study gut microbiota, including high-throughput 16S rRNA sequencing, metagenomics, and massive bacterial cloning [19][20][21][22][23][24][25][26][27].…”
Section: Ld-like Structures In Intestinal Bacteriamentioning
confidence: 99%
“…Then the lipid droplets on the top were collected and washed for further analysis. 18 The size of LDs was analyzed by a BECKMAN Delsa Nano C particle analyzer (Thermo, USA). Purified LDs were stained with LipidTOX (1:500, v/v) for 30 min and mounted on glass slide for observation with Olympus FV1200 Imaging System.…”
Section: Lipid Droplet Purificationmentioning
confidence: 99%
“…Butyrate is under a wide range of biological functions. Studies have shown that butyrate plays an active role in brain disorders in a variety of neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and Huntington's disease [9][10][11][12]. Sodium butyrate (NaB) is a common form of butyrate.…”
Section: Introductionmentioning
confidence: 99%